Blood Glucose Concentration Pro?le After Prophylactic Administration of Intravenous Dexamethasone for Prevention of Postoperative Nausea and Vomiting in Patients Undergoing Laparoscopic Cholecystectomy Under General Anesthesia - Sai Lakshman Pasupuleti; Abinash Patro; Nirmala Jonnavithula; Srikanth Yelliboina; Hemalatha Bora; Sharmila Chaganti (Academia Anesthesiologica International, 2021)
Dexamethasone has been shown to reduce nausea and vomiting after surgery (PONV), but it can also raise blood glucose levels. The effect of two doses of 2 mg and 4 mg dexamethasone on blood glucose levels, PONV, and analgesia in the first 24 hours after laparoscopic cholecystectomy was investigated in this study. At the time of anesthesia induction, 90 patients were enrolled and randomized to receive either saline (control group) or 2 mg or 4 mg dexamethasone in three groups. At baseline and 1, 2, 4, 6, and 24 hours after induction, blood glucose concentrations were measured. PONV and pain scores score were assessed following extubation at 0, 4, 8, 12, and 24 hours. Blood glucose levels rose dramatically in both the control and dexamethasone classes over time (from a median baseline of 87, 87, and 89.5 mg/dL to a final median of 148.5, 168, and 151 mg/dL. (P < 0.001). For every time, there was no significant change in blood glucose concentration between the groups receiving dexamethasone (2 or 4 mg) and those receiving saline. Groups of Dexamethasone showed lower pain score and PONV levels. Dexamethasone administration (2 and 4 mg) did not change blood glucose levels, but it decreased PONV and pain scores that were significantly low at all times. Dexamethasone prophylactic administration can easily be used for nausea and vomiting without hyperglycemia-related issues.